Incidence of Stroke Subtypes in the North East Melbourne Stroke Incidence Study (NEMESIS): Differences between Men and Women - Thrift, Amanda G.; Dewey, Helen M.; Sturm, Jonathan W.; Srikanth, Velandai K.; Gilligan, Amanda K.; Gall, Seana L.; Macdonell, Richard A.L.; McNeil, John J.; Donnan, Geoffrey A. (Neuroepidemiology, 2009)
Background and Purpose: Incidence rates of stroke subtypes may be imprecise when samples are small. We aimed to determine the incidence of stroke subtypes in a large geographically defined population. Methods: Multiple overlapping sources were used to ascertain all strokes occurring in 22 postcodes (population of 306,631) of Melbourne, Australia, between 1997 and 1999. Stroke subtypes were defined by CT, MRI and autopsy. The Mantel-Haenszel age-adjusted rate ratio (MH RR) was used to compare incidence rates between men and women. Results: We identified 1,421 strokes among 1,337 residents, 1,035 (72.8%) being first-ever strokes. Incidence (number/100,000 population/year), adjusted to the European population 45–84 years, was 197 (95% confidence interval, CI, 169–224) for ischemic stroke (IS), 47 (95% CI 33–60) for intracerebral haemorrhage (ICH) and 19 (95% CI 10–27) for subarachnoid haemorrhage (SAH). Compared with women, men in this age group had a greater incidence of IS (MH RR 1.65, 95% CI 1.39–1.96, p < 0.0001) and ICH (MH RR 1.46, 95% CI 1.01–2.10, p = 0.0420), but lesser rates of SAH (MH RR 0.34, 95% CI 0.16–0.69, p = 0.0031). Conclusions: In this population-based study, the incidence of IS and ICH was greater among men than women, while women had a greater incidence of SAH. More effort may need to be directed at modifying risk factors for IS and ICH in men.